Is Midtrimester Vitamin D Status Associated with Spontaneous Preterm Birth and Preeclampsia? - Wetta, Luisa A.; Biggio, Joseph R.; Cliver, Suzanne; Abramovici, Adi; Barnes, Stephen; Tita, Alan T. N. (American Journal of Perinatology, 2014)
Objective The objective of this study is to evaluate whether midtrimester maternal vitamin D is associated with preeclampsia < 37 weeks or spontaneous preterm birth (SPTB) < 35 weeks.Study Design Nested case–control comprising two case subsets: (1) 100 women with preeclampsia < 37 weeks and (2) 100 women with SPB < 35 weeks. Controls consisted of 200 women delivered between 39 and 40 weeks. Stored maternal serum obtained between 15 and 21 weeks was tested for total 25-hydroxy vitamin D (25-OH D) levels using liquid chromatography-tandem mass spectrometry. Mean 25-OH D levels and prevalence of vitamin D insufficiency (25-OH D < 30 ng/mL) and deficiency (25-OH D < 15 ng/mL) were compared.Results In this study, 89 preeclampsia, 90 SPTB cases, and 177 controls had valid measurements. Mean midtrimester vitamin D was not significantly different between women with preeclampsia (27.4 ng/mL ± 14.4) and controls (28.6 ± 12.6) (p = 0.46), or SPTB (28.8 ± 13.2) and controls (p = 0.92). After adjusting for potential cofounders, neither vitamin D insufficiency (adjusted odds ratio [OR], 1.1; 95% confidence interval [CI], 0.6–2.0) nor deficiency (adjusted OR, 1.4; 95% CI, 0.7–3.0) was significantly associated with preeclampsia. Likewise, SPTB was not significantly associated with either vitamin D insufficiency or deficiency (adjusted OR, 0.8; 95% CI, 0.4–1.4, adjusted OR, 1.3 or 95% CI, 0.6–3.0, respectively).Conclusion Midtrimester maternal vitamin D was not significantly associated with preeclampsia < 37 weeks or SPTB < 35 weeks.
Keywords: adverse; 25-hydroxy vitamin D; preeclampsia; preterm birth